Protease-activated receptor-4: a novel mechanism of inflammatory pain modulation - Asfaha, S (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Protease-activated receptor-4 (PAR(4)), the most recently discovered member of the PARs family, is activated by thrombin, trypsin and cathepsin G, but can also be selectively activated by small synthetic peptides (PAR(4)-activating peptide, PAR(4)-AP). PAR(4) is considered a potent mediator of platelet activation and inflammation. As both PAR(1) and PAR(2) have been implicated in the modulation of nociceptive mechanisms, we investigated the expression of PAR(4) in sensory neurons and the effects of its selective activation on nociception. EXPERIMENTAL APPROACH AND KEY RESULTS: We demonstrated the expression of PAR(4) in sensory neurons isolated from rat dorsal root ganglia by reverse transcription-polymerase chain reaction and immunofluorescence. We found that PAR(4) colocalized with calcitonin gene-related peptide and substance P. We also showed that a selective PAR(4)-AP was able to inhibit calcium mobilization evoked by KCl and capsaicin in rat sensory neurons. Moreover, the intraplantar injection of a PAR(4)-AP significantly increased nociceptive threshold in response to thermal and mechanical noxious stimuli, while a PAR(4) inactive control peptide had no effect. The anti-nociceptive effects of the PAR(4)-AP were dose-dependent and occurred at doses below the threshold needed to cause inflammation. Finally, co-injection of the PAR(4)-AP with carrageenan significantly reduced the carrageenan-induced inflammatory hyperalgesia and allodynia, but had no effect on inflammatory parameters such as oedema and granulocyte infiltration. CONCLUSIONS AND IMPLICATIONS: Taken together, these results identified PAR(4) as a novel potential endogenous analgesic factor, which can modulate nociceptive responses in normal and inflammatory conditions.